Pemanfaatan Media Puzzle terhadap Peningkatan Kemampuan Kognitif pada Anak Usia 5-6 Tahun - Zulfiany Thomeng; Wahira Wahira; Andi Asrifan; Herlina Herlina (MAN 4 Kota Pekanbaru, 2026)
This research is motivated by the low cognitive abilities of children aged 5-6 years at TK Nurun Alanur Makassar, caused by the use of less varied learning media. The aim of this study is to describe and analyze holistically how the use of puzzle media can contribute to improving children's cognitive abilities, specifically in aspects of logical thinking, problem-solving, concentration, and visual-spatial skills. This study employs a descriptive qualitative approach. Data were collected through observation, semi-structured interviews, and documentation, and then analyzed using the Miles and Huberman model. The results show that the implementation of puzzle media is carried out through three systematic stages: planning, implementation, and evaluation. Based on the theoretical foundations of Piaget, Vygotsky, and Bruner, it was found that the use of puzzles significantly optimizes logical thinking skills through the assimilation-accommodation process and enhances problem-solving strategies through scaffolding support within the Zone of Proximal Development (ZPD). In conclusion, puzzle media is effective in facilitating children's cognitive development through active and enjoyable direct learning experiences.